The South Asian millipede genus Chondromorpha Silvestri, 1897 (Diplopoda, Polydesmida, Paradoxosomatidae, Sulciferini): redescriptions and synonymies - Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2017)
The South Asian millipede genus Chondromorpha Silvestri, 1897 is diagnosed and its relationship with Parchondromorpha Jeekel, 1980 is established. The species C. atopus (Chamberlin, 1920) and C. indus (Chamberlin, 1920), as well as the subspecies C. kelaarti kelaarti (Humbert, 1865), C. kelaarti longipes (Verhoeff, 1936) and C. kelaarti valparaiensis (Carl, 1932) are recognised as junior synonyms of C. kelaarti (Humbert, 1865), thereby reducing the total number of Chondromorpha spp. in India to four: C. kaimura Turk, 1947, C. kelaarti, C. mammifera Attems, 1936 and C. severini Silvestri, 1897 (the type-species). Two species, C. kelaarti and C. mammifera, are redescribed and illustrated in detail. All four Indian Chondromorpha spp. are keyed, and the known distribution records of C. kelaarti and C. mammifera are mapped.